The Development Of Teaching Model “Arlo Framework Gamification” In Basic Teaching Skill - Anwar, Saiful; Sesriyani, Lodya; Rusmaini, Rusmaini (International Journal of Educational Research & Social Sciences, 2022)
This study aims to develop a gamification learning model as an effective learning model to use during a pandemic which is 100% held in online learning. This development is carried out by considering the needs of students in economic education in pursuing the Basic Teaching Ability course which is a prerequisite course for participating in the field practice program which is mandatory for all education faculty students. This research adopts Marczewski's Gamification Framework which consists of 8 questions, namely 1) what is being gamified; 2) why is it being gamified; 3) who are the users; 4) how is it being gamified; 5) analytics are set up; 6) tested with users; 7) acted on feedback; and 8) released the solution. There are 25 students in this study. Furthermore, the result of this study finds 8 types of mechanics, 8 badges, and 4 trophies. There are 7 students who get platinum level, 10 students get gold level, 5 students get silver level, and the remaining 4 students get bronze level. In addition, there is an increase in the students' pretest and posttest from 66.28 to 82.20.